Peran Tokoh Agama Dalam Mengatasi Perjudian Ibu Rumah Tangga Di Desa Cengal OKI - Yolen Satria Gustama; Choriyah Choiriyah; Mohd Aji Isnaini (ScidacPlus, 2023)
The behavior of housewives who commit deviations in the form of gambling that occurs in Cengal OKI village. The problem in this research in general is what is the role of religious leaders in dealing with housewives' gambling in Cengal OKI village? The general aim of this research is to find out and analyze the role of religious leaders in dealing with housewives' gambling in Cengal OKI village. This research is included in the field research category, the type of data used is qualitative and consists of primary and secondary data. Data collection techniques consist of observation, interviews and documentation, for data analysis, interpretation, source criticism, qualitative description and qualitative and comparative description are carried out. The research findings are: First, the factors that involve housewives gambling in Cengal OKI village are the feeling of boredom felt by housewives, inadequate family economy, invitations from fellow housewives, addiction that cannot be stopped and a sense of satisfaction. What is felt when playing gambling? Secondly, what the Cengal OKI village religious leaders did to overcome the gambling of housewives was to start by carrying out routine recitations which were held every Thursday and Saturday at the mosque. Take a direct approach with village officials, approach through the family, and take legal action in collaboration with the authorities, through the Village Head and other village officials. And third, the response of mothers who were involved in gambling to the actions of these religious figures was a desire to make changes either individually or as a community group. Apart from preventing recurrence, it is hoped that there will be a solution provided by religious leaders and the village government.